The truth in Almodóvar's melodramatic moment: the curious interplay between melodrama and reality in High Heels. Issue 3 (1st September 2016) - Süner, Ahmet
Abstract: This article attempts to show how Almodóvar's melodrama treats both reality and melodrama as if they belonged to the same ontology and destroys the boundaries between them. The essay is an effort to locate both the emotionality and the irony of Almodóvar's melodrama, and particularly of his High Heels, in the intricate relationship between the notion of reality and the genre of melodrama, and to demonstrate how the ironic and the melodramatic modes supplement and reinforce each other despite their apparent opposition. It uses Peter Brooks' and Henry James' observations on nineteenth-century melodrama as a launching pad for a discussion of the ways in which Almodóvar revises the genre of melodrama at the junction between the twentieth and twenty-first centuries. The second half of the essay is dedicated to an analysis of High Heels, which illustrates the ambivalent relationships between reality and performance and between ironic and melodramatic spectatorship.